Potential of the VIR Spinach collection for use in breeding - E. G. Kiselev; D. V. Sokolova (Овощи России)
Relevance. Spinach (Spinacia oleracea L.) is an economically important vegetable crop grown all over the world. This is an annual, cold-resistant and early-ripening crop, cultivated both in protected and open ground. Therefore, there is a need for a wide diversity of varieties and hybrids adapted to specific conditions. The State Register of Breeding Achievements of the Russian Federation contains 67 varieties and hybrids of spinach, of which 66% are foreign hybrid selection. The creation of domestic spinach hybrids is complicated by the lack of well-studied initial material: aligned genotypes of the gynoecic type, combining high yield, early maturity and rich biochemical composition.Materials and Methods. Genetic diversity of crops – potential for breeding and active study in the light of modern knowledge and technologies. The spinach collection collected at the Vavilov All-Russian Institute of Plant Genetic Resources (VIR), which has a 90- year history, includes 744 samples and is the largest in the world. It is unique in the diversity and origin of its accessions.Results. The collection contains high-yielding, early-ripening, late-blooming genotypes; lines with a predominance of the female type of flowering, polyploids are being created. Characteristic groups have been created based on plasticity and high content of valuable biochemicals. As a result of many years of comprehensive study of the spinach collection, the genotypes recommended for inclusion in breeding schemes were identified.Conclusion. The diverse, well-studied gene pool of spinach preserved at the institute is capable of providing unlimited opportunities for breeding and meeting the needs of the country's population, enriching the diet with leafy crop rich in pigments, lutein and protein, with a high content of phenolic elements and antioxidant activity.